The Sources and Causes of Social Threats to Personality, Society and State - Margulyan, Yakov (Journal of Sociology: Bulletin of Yerevan University, 2012)
In the article the author marks the need of sociological research for problems of the social safety, arising social dangers and threats to the population of the country. Then Professor Margulyan considers such terms as "danger" and "threat" in the context of researching terms "cause" and "risk". The author focuses on the idea that only democratic transformations of our society can eliminate revolts and other conflicts.